The Analysis of Metaphorical Domain on English “Stab Verb” in Corpora - LaOde Achmad Suherman (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Metaphor as part of language is taking special place on Semantics studies which is unique and needs more logical thinking in interpretation. The objective of this research was to ascertain the kinds of metaphorical domains of English stab verb in corpora. The data of this research consist of American English and British English which were mainly taken from two corpora, Corpus of Contemporary American English (COCA) and British National Corpus (BNC).  The result of this research indicated that, there were source domain and target domain that were employed on the semantic construction of English Stab verb. Source domain ascertained from the semantic roles which lied on the construction of stab verb, they are Agent, Target and Manip, while target domain consists of twenty noun phrases they are: eyes, looks, words, voice, question, guilt/ remorse, sadness, anger, pain, memory, fear, panic, light/ flash, ray, dark, air, sound and directions. Most of these nouns were mapped as Manip or stabbing instrument while dark, air, and direction were mapped as the stabbing target.